Effect of surface free energy on water absorption of roller-compacted concrete pavement containing calcium stearate powder. Issue 4 (3rd April 2023) - Lotphi, Ali Mohammad; Modarres, Amir
Abstract : The impact of surface free energy (SFE) on water absorption of roller compacted concrete pavement (RCCP) containing calcium stearate powder with different water to cement (w/c) ratios, was investigated. For this purpose, 60 cylindrical specimens were prepared with various percentages of calcium stearate powder. Water absorption, contact angle and air void tests were performed, and SFE values were calculated for various specimens. Accordingly, the addition of calcium stearate powder to RCCP reduced water absorption and SFE while increasing the contact angle. The air void content in RCCPs increased by adding hydrophobic powder. The computed tomography scans showed that the increase of voids was mainly due to the increase in number of pores with a diameter of less than 10 µm. Besides, a relationship between SFE and voids was proposed for RCCPs with different w/c ratios. This relationship indicated that with increasing the percentage of voids, the SFE decreases, which reduces capillary suction and water absorption.